Combining biological agents and chemotherapy in the treatment of cholangiocarcinoma. Issue 4 (April 2011) - Jensen, Lars Henrik; Jakobsen, Anders
The nonsurgical treatment of cholangiocarcinoma has seen major changes within the last few years. A multidisciplinary approach is the cornerstone in planning optimal treatment, but despite several examinations the diagnosis is often based on a certain probability, and histopathological confirmation is not always possible. Chemotherapy is effective and the combination of cisplatin and gemcitabine is considered a standard treatment of inoperable cholangiocarcinoma. Biological targeted treatment to date has minor effect when given as monotherapy, but some of the drugs hold promise as an adjunct to chemotherapy. It should, however, be noted that most of the trials are based on few patients, and thus far the literature does not allow for a conclusion as to the role of biological treatment on cholangiocarcinoma. This situation calls for well-designed randomized trials, and international cooperation as well as marker-driven therapy seems mandatory for treatment progress within a reasonable time.